Efektivitas Penggunaan Whatsapp sebagai Media Pembelajaran Online pada Mata Pelajaran Fikih - Nasrudin, Abdul Kholik (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
The realization of the quality of the learning is inseparable from the role of an educator who is constantly trying to provide learning that can be easily learners to understand. Educators can make the process of learning using the internet and other supporting application such as e-mail, app zoom, whatsapp and others. The use of the internet, this will certainly help educators and learners in the learning process online. The focus of the research to be studied by the researcher, namely : 1) How the Effectiveness of the use of your WhatsApp media, as the media of learning online class X In Senior High School Sunan Kalijaga Kranding on the subjects of Fiqh 2) Anything barriers in Online learning, class X in Ma Sunan Kalijaga Kranding with the use of WhatsApp media on the subjects of Fiqh, the Results of this study is to get an idea of how the implementation of online learning in a pandemic such as this, the researchers conducted this study in the Senior High School Sunana Kalijogo Kranding Mojo Kediri, which the agency also participated suppress the spread of corona virus so as not to spread widely in Madrasaha Aliyah. The subject of research are the learners and the educators Senior High School Sunan kalijogo. The results of this study indicate that 1) After the authors do some research about the effectiveness of your whatsapp media as a medium of online learning in Ma Sunan Kalijogo on the pandemic, online learning is effective as a replacement for media learning in the delivery of the material, and also been able to help students in the implementation of learning on the subjects of fiqh with the good. 2) There are several obstacles that occur in online learning, such as the disruption sinal, internet quota, luggage HP is minimal, it is difficult to understand the material, it is difficult to know the seriousness of the students and inadequate facilities.